Informal assisted desistance among justice-involved young substance abusers - Arseneault, Catherine (Understanding desistance from crime and social and community (re)integration, 2024)
McNeill and colleagues (2012a and 2012b) formulated eight principles to consider in ensuring that interventions to support desistance from crime are consistent with the current state of scientific knowledge on this subject. For many adolescents and young adults, their trajectory of psychoactive substance use (or abuse or addiction) is closely tied to that of their criminality. It is therefore interesting to examine if, and how, these principles are actualized in their desistance from crime and, incidentally, in their addiction recovery process. While relying on these main principles that support the desistance from crime process, this chapter substantiates the perspectives of 34 justice-involved adolescents and young adults (16 to 35 years old) in terms of interventions of informal assisted desistance agents that proved to be particularly significant in their trajectory. Some of the principles put forward by McNeill and his colleagues show through in their accounts. But, as mentioned by Healy (2020), some of McNeill and colleagues’ principles intersect which can complicate their empirical validation. Other winning conditions were also mentioned by the participants in the study, such as being referred to other services and the importance of the temporality of the interventions.